2006
DOI: 10.1248/cpb.54.740
|View full text |Cite
|
Sign up to set email alerts
|

Three New Pentacyclic Triterpenes and Some Flavonoids from the Fruits of an Indian Ayurvedic Plant Dendrophthoe falcata and Their Estrogen Receptor Binding Activity

Abstract: Dendrophthoe falcata (LINN. f.) ETTING. (Syn: Loranthus longiflorus DESR., Loranthus falcatus LINN. f.; Fam. Loranthaceae) is known as 'Vanda' in the Indian Ayurvedic System of Medicine. 1) D. falcata is a large bushy parasitic plant that grows on a variety of host plants in deciduous forests throughout India.2) The entire plant is medicinally important and is used extensively in traditional medicine as an aphrodisiac, astringent, narcotic, diuretic, and for the relief of asthma, menstrual disorders, and pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…42 As for kaempferol, its glyco-conjugated derivative kaempferol-3-O-a-L-rhamnopyranoside (42), found in Dendrophthoe falcata, a plant used in Indian ayurvedic medicine, also proved to be a ERb-selective ligand. 74 Isoflavone derivatives, which are generally abundant in soy foods, often show some ERb selectivity. Some of them, such as daidzein (43) and biochanin A (44) ( Fig.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…42 As for kaempferol, its glyco-conjugated derivative kaempferol-3-O-a-L-rhamnopyranoside (42), found in Dendrophthoe falcata, a plant used in Indian ayurvedic medicine, also proved to be a ERb-selective ligand. 74 Isoflavone derivatives, which are generally abundant in soy foods, often show some ERb selectivity. Some of them, such as daidzein (43) and biochanin A (44) ( Fig.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Its HMBC cross peak to C-11 established its placement at C-11. The relative stereochemistry at C-1, C-3 and C-11 was assigned based on the comparison of the 1 H and 13 C chemical shifts as well as the coupling constant values with those of related triterpenes; it was confirmed by the NOESY experiment (Topçu and Ulubelen 1999; Mathias et al 2000; Chiang and Kuo 2001; Mallavadhani et al 2006; Mohamed 2014). The NOESY cross peaks of H-1 to H-3, H-5 and H-9 as well as H-9 to 11-OCH 3 , H 3 -27 and H 3 -30 indicated that these protons were present on the same side of the molecule.…”
Section: Resultsmentioning
confidence: 88%
“…The known compounds were identified by analysing the spectroscopic data (1D and 2D NMR) and comparing their data with those in the literature to be α -amyrin acetate ( 1 ) (Virgilio et al 2015), α -amyrin ( 2 ) (Virgilio et al 2015), 3 β -acetoxy-20-taraxasten-22-one ( 3 ) (Ramadan et al 2009; Ahmed 2010), 3 β -acetoxy-11 α -methoxy-olean-12-ene ( 4 ) (Kuo and Chiang 2000; Mallavadhani et al 2006; Barbosa et al 2010), 3 β -acetoxy-11 α -methoxy-12-ursene ( 5 ) (Mathias et al 2000; Barbosa et al 2010), 11-oxo- α -amyrin acetate ( 6 ) (Fingolo et al 2013), 11-oxo- β -amyrin acetate ( 7 ) (Fingolo et al 2013), palmitic acid ( 8 ) (Ajoku et al 2015), stigmast-4,22-diene-3,6-dione ( 9 ) (Itokawa et al 1973), stigmast-4-ene-3,6-dione ( 10 ), stigmasterol ( 12 ) (Mohamed and Ibrahim 2007; Kamboj and Salujai 2011; Chaturvedula and Prakash 2012), β -sitosterol ( 13 ) (Al-Musayeib et al 2013), stigmast-22-ene-3,6-dione ( 14 ) (Wei et al 2004), stigmastane-3,6-dione ( 15 ) (Wei et al 2004; Lim et al 2005), 3 β ,21 β -dihydroxy-11 α -methoxy-olean-12-ene ( 16 ) (Cáceres-Castillo et al 2008), 3 β -hydroxy-11 α -methoxyurs-12-ene ( 18 ) (Fujita et al 2000), 6-hydroxystigmast-4,22-diene-3-one ( 19 ) (Kontiza et al 2006; Georges et al 2006), 6-hydroxystigmast-4-ene-3-one ( 20 ) (Kontiza et al 2006; Georges et al 2006) and β -sitosterol-3- O - β -D-glucopyranoside ( 22 ) (Khatun et al 2012). …”
Section: Resultsmentioning
confidence: 93%
“…Previous studies showed that pentacyclic triterpenes from fruits and plants could increase estrogen receptor activities20 and synthetic triterpenes has been identified as ligands for the PPARγ21. In addition, reporter gene assays showed that oleanolic acid increased PPARα activity in spontaneously transformed keratinocyte cell line HaCaT and CV-1 cells22.…”
Section: Discussionmentioning
confidence: 97%